2008
DOI: 10.1128/jvi.02760-07
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Dynamics of Hepadnavirus Reverse Transcriptase during Protein-Primed Initiation of Reverse Transcription: Effects of Metal Ions

Abstract: Reverse transcription in hepadnaviruses is primed by the viral reverse transcriptase (RT) (protein priming) and requires the interaction between the RT and a specific viral RNA template termed . Protein priming is resistant to a number of RT inhibitors that can block subsequent viral DNA elongation and likely requires a distinct "priming" conformation. Furthermore, protein priming may consist of two distinct stages, i.e., the attachment of the first deoxynucleotide to RT (initiation) and the subsequent additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(78 citation statements)
references
References 57 publications
11
67
0
Order By: Relevance
“…Independent TP and RT domains are known to trans-complement each other to carry out the protein priming reaction using the TP domain as a protein primer to initiate DNA synthesis (1,25,27). When the priming reactions were carried out in the presence of Mn 2ϩ , which is known to stimulate priming relative to Mg 2ϩ (27), we found, surprisingly, that the RT domain, as well as TP, acted as a protein primer for initiating DNA synthesis (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Independent TP and RT domains are known to trans-complement each other to carry out the protein priming reaction using the TP domain as a protein primer to initiate DNA synthesis (1,25,27). When the priming reactions were carried out in the presence of Mn 2ϩ , which is known to stimulate priming relative to Mg 2ϩ (27), we found, surprisingly, that the RT domain, as well as TP, acted as a protein primer for initiating DNA synthesis (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, a truncated DHBV RT protein, MiniRT2, with deletion of the entire RNase H domain, the N-terminal third of the TP domain, and most of the spacer, retains ε RNA binding and protein priming activity but no longer requires the host chaperones (55). Recently, we reported that the divalent metal ions, Mg 2ϩ versus Mn 2ϩ , have a dramatic effect on protein priming, including the overall priming efficiency, the template and nucleotide specificity, and the transition from initiation to polymerization, further attesting to the multiple RT conformational transitions that occur during protein priming (27).…”
mentioning
confidence: 99%
See 3 more Smart Citations